A feedforward-feedback-based reactor power decoupling control strategy for multi-modular nuclear power plants. (February 2022) - Wu, Shifa; Nuerlan, Areai; Wan, Jiashuang; Wang, Pengfei; Su, G.H.
Abstract: Multi-modular nuclear power plants (MMNPPs) comprise of several SMRs working in parallel, a common steam header and one or more steam consuming units. The reactor units in this type of plant may share different portion of load and their power may interfere with each other due to a coupling effect through the common steam header. Hence, the load following characteristics of MMNPPs are different from that of single reactor plants. Investigation results show that the coupling effect between load following reactors (LFRs) and fixed power reactors (FPRs) affects the operation of the latter ones during load following or power compensation process. This is not favorable due to the extra movement of the control rods and valves may increase the risk of related accidents. In this research, a setpoint feedforward-feedback header steam pressure control method is proposed to decouple the power output of LFR units and FPR units. Control performance of the decoupling control method is evaluated and made comparison to that of conventional header steam pressure control method. Results demonstrated that the proposed reactor power decoupling control method shows better control performance than the conventional control method, with faster load following speed of the LFR and smaller overshoots of the header steam pressure, eventually keeping the FPR barely disturbed during the transients. This proposed reactor power decoupling control strategy will improve the operation performance, safety and reliability of the MMNPPs.